Silk Route to the Acceptance and Re-Implementation of Bacteriophage Therapy-Part II - Expert round table on acceptance and re-implementation of bacteriophage therapy; Wilbert Sybesma; Christine Rohde; Pavol Bardy; Jean-Paul Pirnay; Ian Cooper; Jonathan Caplin; Nina Chanishvili; Aidan Coffey; Daniel De Vos; Amber Hartman Scholz; Shawna McCallin; et al. (MDPI AG, 2018)
This perspective paper follows up on earlier communications on bacteriophage therapy that we wrote as a multidisciplinary and intercontinental expert-panel when we first met at a bacteriophage conference hosted by the Eliava Institute in Tbilisi, Georgia in 2015. In the context of a society that is confronted with an ever-increasing number of antibiotic-resistant bacteria, we build on the previously made recommendations and specifically address how the Nagoya Protocol might impact the further development of bacteriophage therapy. By reviewing a number of recently conducted case studies with bacteriophages involving patients with bacterial infections that could no longer be successfully treated by regular antibiotic therapy, we again stress the urgency and significance of the development of international guidelines and frameworks that might facilitate the legal and effective application of bacteriophage therapy by physicians and the receiving patients. Additionally, we list and comment on several recently started and ongoing clinical studies, including highly desired double-blind placebo-controlled randomized clinical trials. We conclude with an outlook on how recently developed DNA editing technologies are expected to further control and enhance the efficient application of bacteriophages.